2020
DOI: 10.1097/gox.0000000000003156
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Correction of the Whistling Deformity in Secondary Cleft Lip Reconstruction

Abstract: Background: Following primary repair of a cleft lip, patients present with many facial deformities. One of the commonly observed sequelae of cleft lip repair is a whistling deformity. This retrospective study was carried out to evaluate the outcomes following correction of whistling deformities in secondary cleft lip reconstruction. Methods: We retrospectively reviewed the hospital records of patients with various whistling deformities who underwent rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Other cases showed inconspicuous scars. 7 While Baum et al 8 reported that a hematoma was found in one patient (7%) and a feeling of pressure in four patients (27%). Another patient had a repeated pain in the lip area (7%).…”
Section: Meta Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Other cases showed inconspicuous scars. 7 While Baum et al 8 reported that a hematoma was found in one patient (7%) and a feeling of pressure in four patients (27%). Another patient had a repeated pain in the lip area (7%).…”
Section: Meta Analysismentioning
confidence: 96%
“…Of the 30 patients, 21 were very satisfied with their outcomes, while seven patients graded their outcomes as good. 9 As regard complications : Jian et al 7 reported that the complications of bleeding, infection, or dehiscence were not found. All patients developed mild to moderate postoperative edema of the upper lip, with 29 cases (21.3%) developing conspicuous scars.…”
Section: Meta Analysismentioning
confidence: 99%